Julian Assange, WikiLeaks, and the Trickster: A case study of archetypal influence. - Whitmire, Niko (ReVision)
The article presents a case study related to archetypal influence alongwith information on Australian computer programmer Julian Assange. Topics discussed include U.S Army soldier Bradley Manning who was charged with leaking classified document, resignation by Assange's colleague Daniel Domscheit-Berg at non-profit WikiLeaks and the Trickster which has been defined as a god or spirit which exhibits a great degree of intellect.